PENDIDIKAN ISLAM ERA RASULLULLAHHINGGA KHULAFAUR RASYIDIN : ANALISIS HISTORIS MELALUI STUDI LITERATUR - Rahmad Husain Lubis; Musahur Ayyubi; Abdusima Nasution (Halaqah: Journal of Multidisciplinary Islamic Studies, 2025)
This article examines the dynamics and development of Islamic education during the era of Prophet Muhammad (PBUH) and the Caliphs (Khulafaur Rasyidin) through a literature study approach. The focus of this study lies on the values, methods, institutions, and objectives of Islamic education that emerged in the early Islamic period as the foundation of Islamic civilization. This research uses a qualitative method with a library research approach, drawing from both classical and contemporary sources on Islamic education. The findings reveal that education during the Prophet’s era emphasized moral and faith development through exemplary behavior, dialogue, and habituation, with mosques serving as the main educational centers. During the Caliphs’ period, the system became more organized, leading to the establishment of educational institutions and the expansion of scholars’ and teachers’ roles. In conclusion, the classical Islamic education system during these eras served as the conceptual and moral basis for Islamic education throughout history.